JURNALISME PESANTREN SEBAGAI MEDIA ALTERNATIF: PERLAWANAN KAUM SANTRI TERHADAP HEGEMONI ISI MEDIA MASSA - Minan Jauhari (LP2M IAIN Jember (now UIN Kiai Haji Achmad Siddiq Jember), 2015)
Journalism pesantren could be an alternative movements and cultural that appears in various media to strengthen civil society besides becoming chan-nel activity to spreading ideas and progam-progam pesantren. So can strengthen that alternative media can emerge as answer of maistream culture domination that a bore which is that long considered to have been dictating criteria of culture, moral, and value in society. Media messages from among santri this not only function as voice of ideology his movement, but also invited by readers to act. Although on the other hand the media always perceived as the implement is powerfuland there are the dominant ideology in it. As was supported by Gramsci that hegemony is an effort power lasting done by the group in power. In this case, institutions media give a function hegemony that is continuous producing a cohesive that ideology. Writing it tries to can parse about pesantren journalism as a alternatives medium is a form of resistance people santri to hegemony of the contents of mass media.